Community-oriented primary care for National Health Insurance in South Africa - Shabir Moosa (AOSIS, 2022)
This is a report on Chiawelo Community Practice (CCP) in Ward 11, Soweto, South Africa, a community-oriented primary care (COPC) model for National Health Insurance (NHI) in South Africa, developed by a family physician. A shift to capitation contracting for primary health care (PHC) under NHI will carry risk for providers - both public and private, especially higher number of patient visits. Health promotion and disease prevention, especially using a COPC model, will be important. Leading the implementation of COPC is an important role for family physicians in Africa, but global implementation of COPC is challenged. Cuba and Brazil have implemented COPC with panels of 600 and 3500, respectively. The family physician in this report has developed community practice as a model with four drivers using a complex adaptive system lens: population engagement with community health workers (CHWs), a clinic re-oriented to its community, stakeholder engagement and targeted health promotion. A team of three medical interns: 1 clinical associate, 3 nurses and 20 CHWs, supervised by the family physician, effectively manage a panel of approximately 30 000 people. This has resulted in low utilisation rates (less than one visit per person per year), high population access and satisfaction and high clinical quality. This has been despite the challenge of a reductionist PHC system, poor management support and poor public service culture. The results could be more impressive if panels are limited to 10 000, if there was a better team structure with a single doctor leading a team of 3-4 nurse/clinical associates and 10-12 CHWs and PHC provider units that are truly empowered to manage resources locally.